Conflict of Maritime Delimitation in Exclusive Economic Zone (EEZ) between Indonesia and Vietnam - Herno Della, Rhaptyalyani; Kuntasa, Tanan (Diponegoro University, 2022)
The recent incident in the Natuna waters involving the Vietnamese coast guard and the Indonesian naval patrol has reignited tensions. Both parties claim that their activities were conducted within their respective Exclusive Economic Zones (EEZ). This boundary dispute is likely to persist unless Indonesia and Vietnam reach a mutual agreement regarding their EEZ limits. This article aims to analyze the existing agreement between Indonesia and Vietnam and explore the factors contributing to the prolonged nature of this issue. The delimitation of the border between Indonesia and Vietnam has been prompted by the increasing threats of illegal fishing within Indonesia's sovereign territory in Natuna. Despite being neighboring countries, Indonesia and Vietnam have yet to reach a conclusive decision regarding their EEZ boundaries. This issue persists even after the signing of the continental shelf agreement based on the United Nations Convention on the Law of the Sea (UNCLOS 1982). The EEZ problem in the Indonesia-Vietnam boundaries is compounded by various factors, including economic, diplomatic, and environmental concerns. Resolving this issue requires careful consideration and cooperation between the two nations.